The trouble with pensions: Toward an alternative public policy to support retirement - Yeva Nersisyan; L. Randall Wray (Levy Economics Institute of Bard College, 2010)
Pension funds have taken a big hit during the current financial crisis, with losses in the trillions of dollars. In addition, both private and public pensions are experiencing significant funding shortfalls, as is the government-run Pension Benefit Guaranty Corporation, which insures the defined-benefit pension plans of private American companies. Yeva Nersisyan and Senior Scholar L. Randall Wray argue that the employment-based pension system is highly problematic, since the strategy for managing pension funds leads to excessive cost and risk in an effort to achieve above-average returns. The average fund manager, however, will only achieve the risk-free return. The authors therefore advocate expanding Social Security and encouraging private and public pensions to invest only in safe (risk-free) Treasury bonds - which, on average, will beat the net returns on risky assets.
Keywords: 330; Rentenfinanzierung; Pensionskasse; Bankenaufsicht; Gläubigerschutz; USA